Specific and Sensitive Detection of Enterobacter mori Using Reliable RT-PCR - Lou, M M (Plant disease, 2011)
Enterobacter mori, the causal agent of bacterial wilt in mulberry, is becoming a serious disease in mulberry orchards in China. Because no effective control strategy has been devised for this disease, the reliable screening of mulberry material for latent infection became necessary. Hence, a fast polymerase chain reaction (PCR) assay for the detection of E. mori was developed in this study. The primers were designed within regions of the RNA polymerase β-subunit (rpoB) gene. The method is fast and simple and showed 100% sensitivity (no false negatives) and 100% specificity (no false positives), which was tested with 4 representative E. mori strains, 9 Enterobacter type strains, 2 strains of the other major mulberry bacterial pathogens (Ralstonia solanacearum and Pseudomonas syringae pv. mori) in China, 7 strains of other plant-associated pathogens, and 50 unidentified epiphytic bacterial isolates from mulberry plants. The real-time PCR assays reliably detected the DNA at at least 10 fg/μl and the bacterial cells at 102 CFU/ml from mulberry shoots and roots suspension. The strong positive reaction in testing of all symptomatic plants (with 100% positive) and parts of asymptomatic latent infected plant samples (with 36.4% positive) provided proof that this method is reliable and sensitive and suitable for screening plant material with latent infections of E. mori